2007
DOI: 10.1007/s10565-006-0078-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological aspects of cyclophosphamide and ifosfamide induced hemorrhagic cystitis; implication of reactive oxygen and nitrogen species as well as PARP activation

Abstract: Cyclophosphamide (CP) and ifosfamide (IF) are widely used antineoplastic agents, but their side-effect of hemorrhagic cystitis (HC) is still encountered as an important problem. Acrolein is the main molecule responsible of this side-effect and mesna (2-mercaptoethane sulfonate) is the commonly used preventive agent. Mesna binds acrolein and prevent its direct contact with uroepithelium. Current knowledge provides information about the pathophysiological mechanism of HC: several transcription factors and cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
182
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(196 citation statements)
references
References 33 publications
11
182
0
3
Order By: Relevance
“…These can be demonstrated within 24 h of a single dose [18]. The urotoxicity of CP is thought to be due to the formation of acrolein that damages the urothelium [19,20]. In accordance with other studies, the damage caused in this study by CP to the structure of the bladders increased as the dose rose.…”
Section: Discussionsupporting
confidence: 87%
“…These can be demonstrated within 24 h of a single dose [18]. The urotoxicity of CP is thought to be due to the formation of acrolein that damages the urothelium [19,20]. In accordance with other studies, the damage caused in this study by CP to the structure of the bladders increased as the dose rose.…”
Section: Discussionsupporting
confidence: 87%
“…It has been already demonstrated that CP-induced bladder damage involves peroxynitrite formation and protein nitration. 35,36 It is noteworthy to mention that in the present study, CP treatment resulted in marked decrease in the activity of SOD, and pretreatment with AG almost completely prevented the loss of activity as well as reduced bladder damage.…”
Section: Discussionsupporting
confidence: 56%
“…The primary toxic mechanism involves direct action of acrolein in the proximal tubule, and the secondary action of aldophosphamide -toxic nitrogenous and alkylating compounds -are responsible for the generation of reactive oxygen species. (15,16) This metabolism of cyclophosphamide induces the release of inflammatory cytokines and reactive oxygen species resulting in lipid peroxidation of the cell membrane and consequently, renal injury. (15,16) Thus, the administration of cyclophosphamide chemotherapy induced AKI in rats, which was characterized by reduced glomerular filtration rate, evidenced by a decrease in creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…(15,16) This metabolism of cyclophosphamide induces the release of inflammatory cytokines and reactive oxygen species resulting in lipid peroxidation of the cell membrane and consequently, renal injury. (15,16) Thus, the administration of cyclophosphamide chemotherapy induced AKI in rats, which was characterized by reduced glomerular filtration rate, evidenced by a decrease in creatinine clearance. The release of oxidative metabolites confirms the mechanism of tubular damage, such as the radical superoxide and hydroxyl, and of intermediate such as peroxides that result in the consumption of antioxidants reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation